A Qualitative Study in Indonesia Comparing the Institutional and Socio-Economic Roles of Banking and Cooperatives - Aribowo, Wira Ganet; Sari, Syarifah Ratih Kartika (Westscience Press, 2025)
The goal of this qualitative study is to compare the roles, operational structures, and socioeconomic contributions of banks and savings and loans cooperatives in Indonesia. Both entities are strategically responsible for supporting the national financial system, especially in providing financial services to the lower middle class. This study uses a case study approach and in-depth interviews with managers of banks and cooperatives in three different areas. The study also found that banks are better at following the law and running their businesses efficiently, while cooperatives are better at building social ties and community-based economic empowerment. However, management and professionalism is a big problem for cooperatives. The results of this study say that to strengthen an inclusive and sustainable financial system in Indonesia, the commercial banking approach and the cooperative social approach must work together.